1998
DOI: 10.1007/s004670050483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone in short children after renal transplantation

Abstract: From 1991 to 1993, 90 children having received a kidney graft with a post-transplantation period of at least 12 months were included in a prospective study carried out in 18 French pediatric centers. After informed consent and randomization, children received recombinant human growth hormone (rhGH) (Genotonorm, Pharmacia peptide hormones) 30 U/m2 per week, either immediately on enrollment, for the treated group, or after 1 year of follow-up for the group serving as a control. After 1 year both groups were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
2
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 55 publications
6
82
2
4
Order By: Relevance
“…The first large randomized clinical study from France involving 90 short children after TPL did not show a significant difference between study and control patients [21]. The number of patients with rejection episodes in both groups was not significantly different.…”
Section: Growth Hormone Treatment After Renal Transplantationmentioning
confidence: 78%
“…The first large randomized clinical study from France involving 90 short children after TPL did not show a significant difference between study and control patients [21]. The number of patients with rejection episodes in both groups was not significantly different.…”
Section: Growth Hormone Treatment After Renal Transplantationmentioning
confidence: 78%
“…A aceleração da VC foi descrita em outros estudos envolvendo uso de hrGH em pacientes com DII e em pacientes sob corticoterapia pós-transplante renal (22,27).…”
Section: Hrgh E Corticoterapia Crônicaunclassified
“…É importante destacar que o controle da doença de base, do quadro inflamatório e o estado nutricional representam fatores importantes na determinação do crescimento destas crianças e conseqüentemente da melhor ou pior resposta ao GH (23,39,40). Um caso isolado de papiledema, sem outros sinais de hipertensão intracraniana benigna, revertido com a suspensão do hrGH, e um caso de epifisiólise da cabeça do fêmur foram descritos, ambos em pacientes pós-transplante renal, existindo questionamento sobre a participação da terapia com hrGH em alguns casos de rejeição do enxerto renal (22,27).…”
Section: Hrgh E Corticoterapia Crônicaunclassified
“…In children with kidney transplants, controlled studies [53] revealed no difference between the GH-treated group and the control group in the incidence of acute rejection. However, a French study [54] reported that more than one acute rejection episode prior to rhGH treatment was a risk factor for subsequent episodes during rhGH treatment. rhGH treatment in GC patients appears to be safe and does not significantly modify the course of disease.…”
Section: Safety Of Rhgh Therapy In Glucocorticoid-treated Patientsmentioning
confidence: 99%